Designing carbonisation solutions for sustainable livelihoods - Somorin, Tosin; Oyedepo, S. O.; Kilanko, O.; Onwordi, P.; Gitau, J. K.; Gebrezgabher, Solomie A. (International Water Management Institute, 2025)
Across Sub-Saharan Africa, millions of households still depend on firewood and charcoal for daily energy needs. Such fuel sources accelerate deforestation, expose users to health risks, and entrench poverty. Yet these same landscapes are rich in underused agricultural residues with untapped energy potential. This technical brief introduces an affordable, low-emission carbonization system designed to convert such residues as maize cobs, palm kernel shells, sawdust, and similar biomass into carbonized products. Engineered for mobility, safety, and multi-feedstock use, the system addresses the limitations of traditional kilns through improved airflow control, insulation, and modular assembly. Field tests in Nigeria confirmed efficient thermal performance and consistent yields of biochar. Beyond its technical merits, the innovation demonstrates how localized engineering, training, and small enterprise engagement can simultaneously advance clean energy access, reduce environmental degradation, and create new income opportunities in rural and humanitarian settings.